Analisis Prediksi Kebangkrutan Bank Syariah Dan Bank Konvensional Dengan Metode Altman Z-Score Modifikasi - Hasbi Assidiki Mauluddi; Sarah Fitri Fauziah (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
The presence of COVID-19 in Indonesia impacts the performance of the CAR, FDR/LDR, and NPF/NPL ratios. If the bank does not improve its performance, the bank will threaten with financial distress, which is the initial stage of bankruptcy. This condition has happened to PT. Bank Muamalat Indonesia and PT. Bank Maybank Indonesia. The bankruptcy prediction model used in this study is the Altman Z-Score Modification to compare bankruptcy scores and the effect of the CAR, FDR/LDR, and NPF/NPL ratios on the Z-Score value of BUS and BUK Non-BUMN with the results of CAR values. BUS Non-BUMN has a positive and significant effect, while the CAR value of BUK Non-BUMN has a positive and insignificant effect. The value of FDR/LDR has a positive and not significant effect. The NPF value has a negative and negligible effect, while the NPL value has a positive and significant impact.